Relationship of clinical assessment of stability and bearing area of maxillary and mandibular denture towards the complete denture wearers satisfaction - Ritonga, Putri Welda Utami; Prabakaran, Luveena Loshini (Universitas Padjadjaran, 2007)
Introduction:Clinical assessment of complete denture by the dentists may differ from the patient’s satisfaction. Dentists will prioritise the clinical aspects of dentures, while patients will prioritise more on their satisfaction. The purpose of this study was to determine the relationship between the stability and bearing area of maxillary and mandibular denture towards the complete denture wearers satisfaction. Methods: This study was a cross-sectional study with purposive sampling method. The subject of this study was as much as 30 people. The research was conducted in each patient’s house to obtained more honest review of the patient’s satisfaction towards their complete dentures without being affected by any clinical environment, and in accordance to the information of their medical records. All the subjects were interviewed using a questionnaire before a clinical evaluation was conducted. The test analysis used was the Fisher test. Clinical examination was used to assess denture stability and bearing area. Evaluation of the patient’s satisfaction level was performed using a questionnaire regarding mastication and comfort. Results:There was a significant association between the clinical evaluation towards the patient’s satisfaction level which were the stability of maxillary denture towards mastication (p = 0.012); and mandibular denture towards mastication (p = 0.029). Whereas no relationship found between maxillary denturebearing area towards comfort (p = 0,051) and mandibular denture-bearing area towards comfort (p =0,547).Conclusion:Stability of maxillary and mandibular denture affected the patient’s mastication satisfaction, whereas bearing area of maxillary and mandibular denture was not affected the patient’s comfort satisfaction.